Process of the Switch Majors of a Group of Peruvians College Students - Nájar Santa Cruz, Kenia Briset (2024)
The article develops the objectives of characterizing the vocational reelection process of a group of ten students from private universities in Metropolitan Lima (Peru) and analyzing their subjective position throughout it. The qualitative research approach with phenomenological design was used and the data collection technique was the semi-structured interview. It was found that the vocational reelection process is composed of three stages: the election, the crisis and the vocational reelection. Likewise, during their first and second vocational choice, the young people assumed a different and opposite subjective position towards social and family demands. This change in subjective position was driven by the vocational crisis, and by the search and analysis of the consequent information.